Pengaruh Motivasi Belajar dan Self Efficacy Terhadap Kemandirian Belajar Siswa pada Mata Pelajaran Praktikum Akuntansi Perusahaan Jasa, Dagang dan Manufaktur Kelas XI Akuntansi Keuangan Lembaga (AKL) di SMK Negeri 1 Negara - I Gede Jaya Putra Negara; Kadek Rai Suwena (Ekuitas: Jurnal Pendidikan Ekonomi, 2023)
This research aims to determine the influence of learning motivation and self efficacy partially and simultaneously on self regulated learning students in the subject of Practicum Accounting for Service, Merchandising and Manufacturing Company class XI AKL at SMK Negeri 1 Negara. This research uses a quantitative approach, causal comparative type. The research population is all students of class XI AKL at SMK Negeri 1 Negara totaling 144 students with a sample 108 respondents obtained using probability sampling with simple random sampling technique. Data collection was carried out through observation, questionnaires and in-depth interviews which were analyzed descriptive and multiple linear regression which were tested through SPSS. The results of the research stated: (1) learning motivation influences self regulated learning, with a Tcount 7.514 > Ttable 1.983 and Sig. 0.000 < 0.05 so that H1 is accepted, (2) self efficacy influences self regulated learning, with a Tcount 3.153 > Ttable 1.983 and Sig. 0.002 < 0.05 so that H2 is accepted, (3) learning motivation and self efficacy simultaneously influence self regulated learning, with a value of Fcount 177.284 > Ftable 3.08 and Sig. 0.000 < 0.05 so H3 is accepted. Self regulated learning students 77.2% influenced by learning motivation and self efficacy, it can be seen that the coefficient of determination is 0.772.